Kekuasaan Presiden, Institusi Informal, dan Pengesahan RUU tentang Badan Pengelola Jaminan Sosial (BPJS) - Utomo, Haryo Ksatrio (UI Scholars Hub, 2017)
This article examines the power exercise of President Susilo Bambang Yudhoyono (SBY) in the discussion of the Social Security Administering Body Bill (BPJS Bill) when the president intervenes the process of deliberating the bill in parliament. In the middle of the process, the President intervened the House through a joint forum of political parties that support the government in the House of Representatives or known as the Joint Secretariat (Setgab) by asking them, which have no official position in the state president’s intervention has limited the power of the House of Representatives that should work independently and be free from any form of executive intervention. The existence of these interventions raises question about the relationship between the executive and the legislature bodies in which presidential intervention can be exercised significantly, whereas since 1998 political reforms aimed at the limitation presidential powers by strengthening parliamentary institution. This article argues that President Susilo Bambang Yudhoyono has the ability to use and maximize the informal institution of the president’s power without any counter from the parliament. This article tries to explain this phenomenon by using the informal institutional approach and political administration, to support the government’s proposal. This paper assumes that the thropology. The informal institution approach explains the informal institutions of the president in Indonesia between the pre-reformation and post-reform periods. Then, the approach of political anthropology discusses the influence of Java’s dominant poli¬tical culture in Indonesia. Both approaches indicate that the Javanese political culture is still a factor as the basis for the application of informal practice of the long-established presidential institution which is continued by SBY. It is clear that he is also influenced by the way of thinking built upon Javanese cultural values. The article also elaborates to prove the influence of Javanese culture in the form of the use of informal institutions in the process of drafting the BPJS Bill by the president.